2006
DOI: 10.1182/blood-2005-06-2596
|View full text |Cite
|
Sign up to set email alerts
|

Point mutations in the juxtamembrane domain of FLT3 define a new class of activating mutations in AML

Abstract: IntroductionFMS-like tyrosine kinase-3 (FLT3) has been shown to be mutated in about one-third of patients with acute myeloid leukemia (AML), representing one of the most frequently occurring mutations in this disease. 1,2 Until now, two distinct clusters of activating mutations are known: FLT3-internal tandem duplications (FLT3-ITDs) in the juxtamembrane (JM) domain in 20% to 25% of patients, and point mutations (PMs) in the tyrosine-kinase domain (FLT3-TKD) in 7% to 10% of patients. [3][4][5][6][7][8][9] Rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
113
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(116 citation statements)
references
References 37 publications
1
113
0
2
Order By: Relevance
“…Their prevalence seems to be lower than 1% in all AML subtypes and has not yet been established in cytogenetically normal AML (CN-AML). 19,20 Lastly, a novel gain-of-function mutation (K663Q), located not in the AL but in the N-terminal part of TKD, has been recently identified in AML. 21 Interestingly, a recent study stressed the importance of functional studies, since among the different FLT3 mutations reported outside the JMD and the TKD, some were not associated with kinase activation, and did not contribute to leukemogenesis.…”
Section: Flt3mentioning
confidence: 99%
See 1 more Smart Citation
“…Their prevalence seems to be lower than 1% in all AML subtypes and has not yet been established in cytogenetically normal AML (CN-AML). 19,20 Lastly, a novel gain-of-function mutation (K663Q), located not in the AL but in the N-terminal part of TKD, has been recently identified in AML. 21 Interestingly, a recent study stressed the importance of functional studies, since among the different FLT3 mutations reported outside the JMD and the TKD, some were not associated with kinase activation, and did not contribute to leukemogenesis.…”
Section: Flt3mentioning
confidence: 99%
“…20,23,24 However, there is increasing evidence suggesting that the downstream cellular responses to FLT3-ITD and FLT3-TKD mutation are not equivalent. In murine bone marrow transplantation models as well as in transgenic mice, FLT3-ITD induces a myeloproliferative disease that closely resembles human chronic myelomonocytic leukemia, and FLT3-TKD an oligoclonal lymphoid disorder with longest latency, but neither FLT3-ITD nor FLT3-TDK mutations induce AML.…”
Section: Flt3mentioning
confidence: 99%
“…(b) Expression of GADD45A mRNA in AML. We determined the average levels of GADD45A mRNA in each AML cluster identified by Valk et al 38 Plot shows normalized expression of GADD45A in each AML cluster (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16) and in the normal control (CD34 þ and normal bone marrow (NBM)) (*Po0.05, # Po0.001, t-test). (c) Cluster details including number of patients, most common abnormality and fold expression change.…”
Section: Flt3-wtmentioning
confidence: 99%
“…1 Recent screens have also identified a range of other point mutations in FLT3 in AML. [2][3][4] FLT3-ITD and FLT3-TKD mutants induce distinct disease states in mouse models 5 and although FLT3-ITD mutations are associated with a poor prognosis, [6][7][8][9] the prognostic implications of FLT3-TKD mutations are less clear. 9,10 The signaling events induced by the activated FLT3 mutants presumably converge to modulate gene expression changes contributing to survival, proliferation and maintenance of differentiation arrest.…”
Section: Introductionmentioning
confidence: 99%
“…Occurring less frequently are additional point mutations in the kinase domain, including N841I (Jiang et al, 2004) and Y842C (Kindler et al, 2005). In addition, novel activating point mutations have been identified in a 16 amino-acid stretch of the FLT3 juxtamembrane, which generally have a weaker transforming potential than FLT3-ITD and tyrosine kinase domain mutants (Reindl et al, 2006). A diagram of FLT3 mutations is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%